2019
DOI: 10.1002/cite.201800199
|View full text |Cite
|
Sign up to set email alerts
|

Reactor Concept for Contactless Kinetic Measurement in Oscillating Droplets via Raman Spectroscopy

Abstract: A millistructured reactor and spectroscopic setup for contactless kinetic measurements in oscillating droplets is presented in this work. The polymerization of acrylic acid serves as a model reaction. Design and construction of the reactor focus on the optical access for Raman measurement, the nearly isothermal behavior, and the preservation of droplets during long‐term reactions with a high increase of viscosity. Another key aspect is the possibility of full automation at a later stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Similar to the widespread application of NIR spectroscopy for in situ monitoring of chemical reactions, particularly polymerisation reactions [23,24], Raman spectroscopy can be employed. Previous research by Klement et al has shown that the integral of the C=C stretching vibration band can be correlated linearly to the acrylic acid (AA) concentration in aqueous solutions from 20 g/L up to 400 g/L [25]. Because the Raman spectrum of isopropyl alcohol does not overlap with this band, the AA concentration could be measured throughout the whole polymerisation reaction.…”
Section: Inline Monitoring and Polymerisation Rate Determinationmentioning
confidence: 99%
“…Similar to the widespread application of NIR spectroscopy for in situ monitoring of chemical reactions, particularly polymerisation reactions [23,24], Raman spectroscopy can be employed. Previous research by Klement et al has shown that the integral of the C=C stretching vibration band can be correlated linearly to the acrylic acid (AA) concentration in aqueous solutions from 20 g/L up to 400 g/L [25]. Because the Raman spectrum of isopropyl alcohol does not overlap with this band, the AA concentration could be measured throughout the whole polymerisation reaction.…”
Section: Inline Monitoring and Polymerisation Rate Determinationmentioning
confidence: 99%
“…It was further developed by the research group of Röder et al. for rapid and slow reactions . This method allows for independently choosing the residence time and screening the chemical process time scale.…”
Section: Droplet-based Reaction Screeningmentioning
confidence: 99%
“…21 It was further developed by the research group of Roder et al for rapid 44 and slow reactions. 45 This method allows for independently choosing the residence time and screening the chemical process time scale. It is necessary for the implementation of the oscillating flow to monitor the slug inside the CFI.…”
Section: Droplet-based Reaction Screeningmentioning
confidence: 99%
“…16 In order to overcome this challenge, a 3-phase microreactor, in which an oscillating droplet is passing a catalyst in a millimetre scaled capillary, was developed. Up to date, such oscillation setups were mainly applied to 2-phase systems [17][18][19][20][21] and in the context of the microfluidic synthesis of nanocrystals 22,23 starting from a solution-phase.…”
Section: Introductionmentioning
confidence: 99%